The Role of Customary Law in Preserving Local Wisdom in the Modern Era - Safina, Ama; Benita, Marsya; Imran, Ali; Yunanda, Bre (Lembaga Penerbitan dan Publikasi Ilmiah Yayasan Pendidikan Tumpuan Bangsa, 2025)
This study aims to explore the role of customary law in preserving local culture amidst the growing challenges of globalization. Using a qualitative approach, the research involves literature review, in-depth interviews, participatory observation, and data analysis to gain a comprehensive understanding of the implementation and challenges of customary law in society. The results indicate that customary law plays a significant role in maintaining and preserving local traditions and cultural values. The community views customary law as a system that aligns more closely with their values, despite the challenges posed by formal positive law and the influence of foreign cultures on the younger generation. To ensure the sustainability of customary law, efforts to integrate customary law with national law are required, as well as involving the younger generation in the preservation of local culture. This study concludes that customary law has great potential in maintaining cultural identity, but its success depends on the commitment of society and support from various stakeholders.